Improving translational studies: lessons from rare neuromuscular diseases - Dominic Wells (The Company of Biologists, 2015)
Animal models play a key role in the development of novel treatments for human disease. This is particularly true for rare diseases - defined as disorders that affect less than 1 in 2000 people in the human population - for which, very often, there are no effective methods of treatment. Pharmaceutical companies are increasingly focussing on the development of therapies for the more than 7000 rare diseases. Because the majority of these are the result of single gene disorders, the exceptional ability to manipulate the mouse genome means that many such studies will take place in the laboratory mouse. But how good are the mouse models and how useful are they in assessing the potential for translational medicine? In this Editorial, I will discuss current difficulties in translational research as well as examples of good laboratory practice and guidelines that are being implemented to improve the translational potential of animal studies in the field of neuromuscular rare diseases. This could represent a potentially useful approach for adoption by other disease fields to achieve a greater success rate in translational studies.